Pengembangan Media Pembelajaran Interaktif Berbasis Canva Berdasarkan Model Discovery Learning Pada Materi Pengolahan Data - Dwiana May Astiningsih; Naila Tsuraya Zahra; Riska Risma Yanti; Alfiana Nurussama; Teten Ginanjar Rahayu (CV. SINAR HOWUHOWU, 2025)
The development of digital technology demands innovation in mathematics education at the elementary school level, particularly regarding data processing topics, which students still find challenging. Low learning interest and a lack of student engagement in understanding the concepts of mean, median, and mode are issues that need to be addressed through the use of interactive learning media. This study aims to develop and test the validity and practicality of